A combined geochemical and isotopic study of the fluids discharged from the Montecatini thermal system (NW Tuscany, Italy). (August 2015) - Capecchiacci, F.; Tassi, F.; Vaselli, O.; Bicocchi, G.; Cabassi, J.; Giannini, L.; Nisi, B.; Chiocciora, G.
Highlights: Water chemistry of the Montecatini thermal system (MTS) indicates a Na–Cl composition. Dissolved gases are dominated by a CO2 -rich gas phase. MTS is fed by meteoric waters with a relatively long (>50 years) circulation. Geothermometric estimations suggest that the fluid reservoir is at T ⩾ 80–90 °C. A new conceptual model of fluid circulation was proposed for MTS. Abstract: The thermo-mineral fluids discharges of Montecatini Terme (Northern Apennines, Tuscany, Italy) have been exploited since the Roman times and despite the fact that this thermal complex is one of the biggest in Europe, the most recent geochemical investigations were published almost 40 years ago. To fill this gap, in this paper a detailed geochemical and isotopic investigation on the main thermal springs and wells from the Montecatini thermal system (MTS) is presented. The chemical and isotopic features of the Montecatini waters suggested that they are mainly controlled by water–rock interaction processes between meteoric water, permeating at depth from the surrounding reliefs (up to 800 m a.s.l.), and the Triassic evaporites (Burano Formation) belonging to the Tuscan sedimentary series. The local stratigraphic and tectonic framework favors an efficient recharge of the hydrothermal reservoir by the meteoric precipitation from a large catchment area and this aspect plays a fundamental role for the longevity of the Montecatini thermal spas, notwithstanding the huge amount of thermal water exploited. The 3 H values indicated that the thermal waters are likely related to a relatively long (>50 years) fluid circulation pattern. Approaching the surface, thermal and saline waters mix with cold and low TDS (Total Dissolved Solids) waters hosted in short, shallow aquifer(s), whose chemistry is dictated by the interaction of rain waters with silico-clastic rocks of low solubility. Geothermometric estimations in the F − –SO4 2− –HCO3 − system suggested the occurrence of a main fluid reservoir at T ⩾ 80–95 °C and P CO2 ∼0.5 bars. Such CO2 pressure is consistent with values estimated for other thermal springs from central-southern Tuscany, being CO2 basically supplied by a deep source. Nevertheless, δ 13 C-CO2 and δ 13 C-TDIC values were lower than those expected for a mantle/thermometamorphic CO2 source. This can be explained by: (i) isotopic fractionation occurring during calcite precipitation and/or (ii) mixing with biogenically derived gases, occurring at relatively shallow depth.